Nitrous oxide production in the Chesapeake Bay. Issue 9 (27th July 2022) - Tang, Weiyi; Tracey, John C.; Carroll, Julia; Wallace, Elizabeth; Lee, Jenna A.; Nathan, Levy; Sun, Xin; Jayakumar, Amal; Ward, Bess B.
Abstract: Estuaries at the global scale are significant but highly uncertain sources of atmospheric nitrous oxide (N2 O), which is an intense greenhouse gas and ozone depletion agent. As the largest estuary in the United States, the Chesapeake Bay is suggested to be a spatially and temporally variable source and sink of N2 O. However, limited observations of N2 O cycling preclude us from estimating and predicting its net N2 O flux. To improve our mechanistic understanding of the processes that control the N2 O flux at the point of production, we applied multiple 15 N tracers ( NH 4 + 15, 15 N‐urea, NO 2 − 15, and NO 3 − 15 ) to separately track N2 O production from nitrification and denitrification under in situ and manipulated O2 concentrations in the Chesapeake Bay. Nitrification was the major N2 O production pathway in oxic waters (up to 7.5 nmol N2 O L −1 d −1 ). In contrast, denitrification dominated N2 O production from hypoxic/anoxic waters (up to 20 nmol N2 O L −1 d −1 ). N2 O production from urea was observed for the first time in estuarine waters. The contribution from urea was small, but interestingly, showed a depth pattern distinct from other N2 O precursors. Experimentally lowering the O2 concentration substantially enhanced N2 O production. Therefore, the expansion of hypoxic and anoxic zones in the Chesapeake Bay under climate change as suggested by some climate models may favor the production of N2 O, potentially providing positive feedback on warming. Overall, our study provides mechanistic constraints on N2 O dynamics that could benefit modeling studies to better estimate the N2 O flux in the Chesapeake Bay and other coastal environments.